Formulation and comparative analysis of polyherbal cough syrup prepared with different palmyrah sweeteners - Mahilrajan, S.; Winston, M.J.; Vijayakumar, T.; Thayalini, T. (University of Vavuniya, 2022)
The purpose of this study was to examine the phytochemical and nutritional analyses of polyherbal cough syrup that had been manufactured and was made with palmyra sweetener and a decoction that containedcoarse dried herbs. Medicinal plants were collected, air-dried, and then used to prepare water and ethanol extracts. Among both extracts, water extract was selected for further study because it contained a high amount of components such as ash, protein, and sugar than ethanol extract. Three different polyherbal syrup was prepared with decoction by using sweeteners such as white sugar (TI), palmyrah jaggery (TII), and sugar candy (TIII). Physicochemical analysis of TII showed a low amount of water content [21.7(±1.01]) (v/v %) and water activity (aw) [0.627(±0.001)]. In addition that it showed significantly higher amounts of nutritional content such as total ash [6.5(±0.35)], total sugar [39.7(±1.08)], crude protein [3.0(±0.2)], and crude fat [0.9(±0.1)] g/100g also mineral content as calcium [415.7(±1.2)], magnesium [264.1(±0.7)], sodium [595.45(±4.8)], potassium [1747.2(±11.7)], phosphorous [359.9(±5.5)] and iron [141.4(±1.1)] (mg/100g) when compared with other syrup as TI and TIII. Therefore cough syrup prepared with decoction and palmyrah jaggery was selected for the studiesas stability and standardization.
Keywords: Polyherbal cough syrup; Decoction; Hot water; Palmyrah sweeteners